The Influence of Using Youtube Social Media on Social Attitude of Elementary School Fifth Grade Students - Ferdianto, Ferry; Sari, Pratiwi Kartika; Ratnawati, Elfrida; Erlina (International Journal of Psychosocial Rehabilitation, 2020)
this study aims to determine whether there is an influence of using YouTube social media on social attitudes of elementary school students fifth-grade students who are limited to social attitudes of discipline, responsibility, tolerance, and courtesy. The sample in this study were three public elementary schools (SDN) in the South Jakarta environment by taking students in fifth grade at each school. The research method used is a survey method to see the influence of using YouTube social media on social attitudes of the elementary school fifth-grade students using simple regression analysis. The results obtained showed that the social attitude of discipline received 22.0%, the social attitude of responsibility obtained 0.92%, the tolerant social attitude obtained 0.33%, and the socially polite attitude gained 0.48%. Conclusions What can be taken in this study is that there is an influence of the use of social media youtube on social attitudes of elementary school fifth-grade students with a result of 0.12%, which is very weak. After the researchers conducted a deepening of the study through interviews obtained 88% results that the factors of parents and teachers were more influential on students’ social attitudes.